2003
DOI: 10.1046/j.1365-2672.2003.02007.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of some abiotic factors on the biological activity of Gluconacetobacter diazotrophicus

Abstract: Aims: The effect of some abiotic factors, dryness, heat and salinity on the growth and biological activity of Gluconacetobacter diazotrophicus, and the influence of a salt stress on some enzymes involved in carbon metabolism of these bacteria is studied under laboratory conditions. Methods and Results: Strain PAL-5 of G. diazotrophicus was incubated under different conditions of drying, heat and salinity. Cells showed tolerance to heat treatments and salt concentrations, and sensitivity to drying conditions. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…GDI has high tolerance to low pH and organic acids and is able to fix nitrogen at pH values as low as 2.5 [ 27 ]. The acidophile Acetobacter aceti has an unusual citric acid cycle (CAC) that is important for acetic acid resistance at low pH [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…GDI has high tolerance to low pH and organic acids and is able to fix nitrogen at pH values as low as 2.5 [ 27 ]. The acidophile Acetobacter aceti has an unusual citric acid cycle (CAC) that is important for acetic acid resistance at low pH [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Such abilities, including its carbohydrate metabolism, auxin biosynthesis, and bacteriocin production, help characterize G. diazotrophicus as a plant growth promoting bacteria (PGPB). These bacteria are also very sensitive to dry conditions, yet present a high tolerance to heat treatments and salt concentrations in culture medium (Tejera et al 2003). Plant growth substances such as salicylic acid, auxins, gibberellins, cytokinins, and abscisic acid are known to modulate the plant response against drought (Farooq et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Gluconacetobacter diazotrophicus is an obligatory aerobe with the ability to fix atmospheric nitrogen (Stephan et al, 1991;Alvarez and Martínez-Drets, 1995), well adapted to extreme conditions such as high sugar concentrations and low pH (James and Olivares, 1997;Chanway, 1998), but also shows a high tolerance to abiotic factors such as heat treatments and salt concentrations in the culture media (Tejera et al, 2003). Results of Dong et al (1994) demonstrated the presence of the N 2 -fixing endophyte (G. diazotrophicus) living in the apoplastic fluid of sugarcane plants, and Fuentes Ramirez et al (1999) confirmed the presence of this bacterium within the xylem and intercellular apoplast.…”
Section: Introductionmentioning
confidence: 99%